Stress Analysis on Single-Crystal Diamonds by Raman Spectroscopy 3D Mapping - Di Liscia, Emiliano Javier (2013)
Results on stress analysis for single-crystal diamonds are presented. Isolated crystals were studied by Raman mapping and depth profiling techniques, using confocal microscopy. Diamonds were deposited on molybdenum and tantalum by hot filament and microwave CVD methods at growth rates between 10 and 30 μm·h−1. Crystals from 10 to 40 μm size were examined. Local stress was evaluated by analyzing the position, broadening and splitting of the 1332 cm−1 Raman peak in a 3D mapping. For the (001) orientation, the most stressed zone was found at the center of the crystal base, close to the interface with the substrate: a Raman peak around 1340 cm−1 was measured, corresponding to a pressure c.a. 3 GPa, according to our dynamical calculations. This peak disappears few microns out of the center, suggesting that this highly concentrated stress sector was the nucleation zone of the crystal. A shifting and slight broadening of the 1332 cm−1 band was observed in the rest of the crystal. The causes of these effects are discussed: they proved not to be due to anisotropic stress but to refractive effects. Same results were found for different crystal sizes and growth rates.